DAYAK IDENTITY ETHNIC CLASH IN PALANGKA RAYA - Ricky Zulfauzan (Prodi Sosiologi FISIP UPR, 2018)
This study describes Dayak ethnic group is the majority ethnic resident of Palangka Raya city and most of Central Kalimantan area. As previously known, Dayak ethnicity is highly open in the matter of social interaction with different ethnic group. This is due to “Huma Betang” philosophy that the Dayak community adhered to. However, ethnic clashes due to intense and heterogenous intertribal interaction process cannot be avoided. For example, in the Dayak community, serving the best food they have is a form of respect towards guests (different ethnicity). Guests eating heartily together with host until none of the food left is an honor for Dayak people. Refusing the invitation to eat is a huge affront for them. However, different condition happens in the case of tradition, interaction, and courtesy of Javanese people. When they are offered invitation to eat, Javanese tends to consider refusing it. Even though they receive it, Javanese will behave as though they are forced to, by leaving a lot still in their plates to avoid presumption of being “serakatan” (avaricious). This paper would offer solution to minimalize the occurrence of ethnic clashes and conflicts in Palangka Raya, as this city is a candidate for new governance capital city of Republic of Indonesia (NKRI). This effort is important so that ethnic conflicts that claimed a lot of lives won't be repeated, as trauma of DayakMadura ethnic conflict during 2000s still well-remembered among Dayak community.